The qualifications and professional competencies of architects on the energy efficiency of buildings. Are they prepared to embrace the 2020 targets? - Fernandes, Sílvia (2014)
The recast Energy Performance of Buildings Directive requires that from 2020 onwards, all new buildings are nearly zero-energy buildings. This new concept requires a strong implementation of sustainable construction methods and techniques as well as the integration of renewable energy technologies in building architecture. Among the stakeholders, architects intervene at an early stage of any building construction process. A survey and expert interviews were conducted, and a review of literature was carried out, followed by a comparative analysis of the structures and degree syllabuses of Portuguese architecture degree courses. The most common problems reported were the lack of dissemination of the EPBD requirements and the need to improve access to regulations, tools and methods, as well as best practices. The conclusion drawn from these results is that it is essential to raise architects awareness towards the important role that they can play in the implementation of these new requirements